The role of female opposition representatives in the 13th parliament - Amirul Azam Asri; Rosyidah Muhamad (Penerbit Universiti Kebangsaan Malaysia, 2023)
The traits associated with the two genders recognized as men's and women's personality, behavior,value, power, and influence are referred to as gender. However, gender inequality is widespread,affecting various areas, including society, the economy, education, medicine, and politics. Women's political participation in society has not received as much attention from researchers as that of men in the political sphere. This is because men are generally more involved in politics than women are in many nations. But there is a significant disparity in the participation of men and women in politics in Malaysia as well. This article will therefore concentrate on the participation of female opposition lawmakers in the 13th parliament from 2013 to 2018. This study aims to uncover the topics that the female opposition in the 13th parliament discussed. The second goal is to examine how the opposition behaved during the 13th parliament, and the third goal is to determine how the female opposition participated during that session. Document analysis from the parliamentary Hansard serves as the primary method in this study's qualitative methodology. The empirical findings show a relationship between the number of parliamentary seats and Pakatan Harapan's victory in the previous General Election. The opposition took an active part in acting as a legislative and representative force. It’s interesting to think that this study will interest and inform many parties more. The public, policymakers, and researchers are a few among them. Besides, this study will introduce the opposition party community, particularly in Malaysia. It is anticipated that the researcher will be able to share expertise and information on the opposition through this study, particularly female opposition.